2017
DOI: 10.1186/s12964-017-0178-x
|View full text |Cite
|
Sign up to set email alerts
|

Kaiso differentially regulates components of the Notch signaling pathway in intestinal cells

Abstract: BackgroundIn mammalian intestines, Notch signaling plays a critical role in mediating cell fate decisions; it promotes the absorptive (or enterocyte) cell fate, while concomitantly inhibiting the secretory cell fate (i.e. goblet, Paneth and enteroendocrine cells). We recently reported that intestinal-specific Kaiso overexpressing mice (Kaiso Tg) exhibited chronic intestinal inflammation and had increased numbers of all three secretory cell types, hinting that Kaiso might regulate Notch signaling in the gut. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…This array was comprised of 76 patient cases of which, 4 were Crohn’s disease tissues, 5 were normal intestinal tissues and the remaining 67 represented intestinal adenocarcinomas and metastatic carcinomas. I mmuno h isto c hemistry (IHC) was performed on this TMA and murine intestinal tissues as previously described [14, 24, 28]. The primary antibodies used were as follows: rabbit anti-Ki67 1:150 (Spring Biosciences, Pleasanton, CA); rabbit anti-ZO-1 1:250 (Santa Cruz, Dallas, TX), mouse anti-Claudin2 1:250 (Abcam, Cambridge, MA), mouse anti-p120 catenin (clone 15D2, [29]), mouse anti-β-catenin 1:10,000 (BD Biosciences, Franklin Lakes, NJ), mouse anti-E-cadherin 1:5,000 (BD Biosciences, Franklin Lakes, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…This array was comprised of 76 patient cases of which, 4 were Crohn’s disease tissues, 5 were normal intestinal tissues and the remaining 67 represented intestinal adenocarcinomas and metastatic carcinomas. I mmuno h isto c hemistry (IHC) was performed on this TMA and murine intestinal tissues as previously described [14, 24, 28]. The primary antibodies used were as follows: rabbit anti-Ki67 1:150 (Spring Biosciences, Pleasanton, CA); rabbit anti-ZO-1 1:250 (Santa Cruz, Dallas, TX), mouse anti-Claudin2 1:250 (Abcam, Cambridge, MA), mouse anti-p120 catenin (clone 15D2, [29]), mouse anti-β-catenin 1:10,000 (BD Biosciences, Franklin Lakes, NJ), mouse anti-E-cadherin 1:5,000 (BD Biosciences, Franklin Lakes, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, expression of the Notch pathway target gene Hes1 was decreased in Kaiso Tg/+ mice [46], hinting at a novel role for Kaiso in regulating cell fate decisions through Notch signalling in the murine intestine. Notably, Kaiso represses the expression of both the Notch1 receptor and the Notch ligand Dll-1 in CRC cell lines [53] but promoted Jagged-1 expression, which is implicated in colon cancer progression. This finding provides an additional mechanism whereby Kaiso may promote CRC and adds another layer of complexity to Kaiso’s role in intestinal homeostasis and colon cancer.…”
Section: A Jack Of All Trades: the Multifaceted Functions Of Kaiso Inmentioning
confidence: 99%
“…In the mice, Kaiso inhibits the expression of Notch1 and Dll1. Consequently, Kaiso-mediated repression of the genes promotes the increase in secretory cells [82]. This finding reveals a novel signaling pathway via Kaiso in regulating Notch-mediated small intestinal homeostasis.…”
Section: Notch Signaling In Isc Homeostasismentioning
confidence: 71%
“…For instance, combined loss of both Dll1 and Hes1 results in increased secretory cell types [21,80,81]. Robinson et al [82] recently reported that the poxvirus and zinc finger transcription factor, Kaiso, regulates the secretory cell lineage in coordination with Notch signaling in intestinal-specific Kaiso-overexpressing mice. In the mice, Kaiso inhibits the expression of Notch1 and Dll1.…”
Section: Notch Signaling In Isc Homeostasismentioning
confidence: 99%